Investment Climate Rating Evaluation: The Case of Ukrainian Economy - Kuznetsova, Svitlana; Vakulich, Maria (Financial Risk and Management Reviews, 2017)
Methodical approaches to the investment climate evaluation have been formed. Methodological tools for assessing the investment attractiveness of the economy have been classified. To create a database to select the most important methods of assessment of the investment climate should undertake a comparative analysis on the target group of potential investors, the depth of research, the frequency of assessment of the investment climate, purpose assessment of the investment climate. International ratings are effective tools that help reduction information asymmetry, and a large number of methods of ranking permit the investor to receive information on all aspects of the investment attractiveness of the state. Rankings are shaping the image of the state, and ignoring the results of the ratings can lead to financial isolation of the state. Information on the methodology of the ratings in most cases is transparent, so the domestic state institutions have the ability to affect the future results of the ratings in the case of related reforms. However, there is no unified model of investment climate evaluation of the national economy, which directly affects the state of the investment climate of Ukraine's economy and the volume of foreign capital in the state. Rating evaluation of the investment climate for the Ukrainian economy has been offered.